Progression-free survival and quality of life in metastatic breast cancer: The patient perspective. (October 2022) - Mertz, Shirley; Benjamin, Christine; Girvalaki, Charis; Cardone, Antonella; Gono, Paulina; May, Suepattra G.; Comerford, Erin; Than, Kyi-Sin; Birch, Kelly; Roach, Meaghan; Myers, Sky; Sasane, Medha; et al.
Abstract: Introduction: Treatment advances for metastatic breast cancer (mBC) have improved overall survival (OS) in some mBC subtypes; however, there remains no cure for mBC. Considering the use of progression-free survival (PFS) and other surrogate endpoints in clinical trials, we must understand patient perspectives on measures used to assess treatment efficacy. Objective: To explore global patient perceptions of the concept of PFS and its potential relation to quality of life (QoL). Materials and methods: Virtual roundtables in Europe and the United States and interviews in Japan with breast cancer patients, patient advocates, and thought leaders. Discussions were recorded, transcribed, and analyzed thematically. Results: Lengthened OS combined with no worsening or improvement in QoL remain the most important endpoints for mBC patients. Time when the disease is not progressing is meaningful to patients when coupled with improvements in QoL and no added treatment toxicity. Clinical terminology such as "PFS" is not well understood, and participants underscored the need for patient-friendly terminology to better illustrate the concept. Facets of care that patients with mBC value and that may be related to PFS include relief from cancer-related symptoms and treatment-related toxicities as well as the ability to pursue personal goals. Improved communication between patients and providers on managing treatment-related toxicities and addressing psychosocial challenges to maintain desired QoL is needed. Conclusion: While OS and QoL are considered the most relevant endpoints, patients also value periods of time without disease progression. Incorporation of these considerations into the design and conduct of future clinical trials in mBC, as well as HTA and reimbursement decision-making, is needed to better capture the potential value of a therapeutic innovation. Highlights: Overall survival benefit combined with good QoL are the most important endpoints for mBC patients. Time without disease progression is meaningful to patients when coupled with no worsening in or improvements in QoL. Quality of life is highly individual and evolves throughout the treatment journey. Surrogate endpoints are confusing; more patient-centered language is needed. Healthcare professionals should account for disease and psychological well-being.